What Do Lost Wallets Tell Us about Survey Measures of Social Capital? - David Tannenbaum; Alain Cohn; Christian Lukas Zünd; Michel André Maréchal (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We validate survey measures of social capital with a new data set that examines whether citizens report a lost wallet to its owner. Using data from more than 17,000 lost wallets across 40 countries, we find that survey measures of social capital - especially questions concerning generalized trust or generalized morality - are strongly and significantly correlated with country-level differences in wallet reporting rates. A second finding is that lost wallet reporting rates predict unique variation in economic development and government effectiveness not captured by existing measures, suggesting this data set also holds promise as a useful indicator of social capital.
Keywords: C93; C83; Z10; O10; 330; social capital; trust; honesty; field experiment; surveys